Identitas Sosial, Kompleksitas Identitas, dan Sinodalitas: Suatu Kajian Lintas Iman dalam Konteks Moderasi Beragama di Indonesia - Yongki Saputra; Juliana Sriana Sinaga (JURNAL PASTORAL KATEKETIK, 2025)
This study aims to analyze the dynamics of interfaith relations in Indonesia by integrating Social Identity Theory (SIT), Social Identity Complexity (SIC), and Pope Francis' synodality. The focus of the study is to understand how social identity categories, identity intersections, and the synodal vision of communion, participation, and mission can enrich the paradigm of religious moderation in a pluralistic society. This study uses qualitative methods with a literature review and content analysis approach to identity theory, empirical findings on interfaith tolerance, and Catholic Church documents. The study was conducted by exploring the key concepts of SIT and SIC, examining social practices of tolerance in the Indonesian context, and describing the pastoral relevance of synodality as a dialogical approach. The results of the study show that religious moderation can develop when religious communities have a natural meeting space, build flexible social identity intersections, and actively engage in mutual listening dialogue as emphasized in the 2021–2023 Synod process. In this context, synodality provides a theological framework for the Church to foster inclusive, creative, and transformative relationships, so that each religion can display its uniqueness in diversity without losing the spirit of brotherhood.